K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

28 tháng 10 2021

Bài 1:

\(1,Sửa:x^3-2x^2+x=x\left(x^2-2x+1\right)=x\left(x-1\right)^2\\ 2,=6\left(x^2+2xy+y^2\right)=6\left(x+y\right)^2\\ 3,=2y\left(y^2+4y+4\right)=2y\left(y+2\right)^2\\ 4,=5\left(x^2-2xy+y^2\right)=5\left(x-y\right)^2\)

Bài 2:

\(1,=x\left(x^2-64\right)=x\left(x-8\right)\left(x+8\right)\\ 2,=2y\left(4x^2-9\right)=2y\left(2x-3\right)\left(2x+3\right)\\ 3,=3\left(x^3-1\right)=3\left(x-1\right)\left(x^2+x+1\right)\)

Bài 3:

\(a,=5\left(x^2+2x+1-y^2\right)=5\left[\left(x+1\right)^2-y^2\right]=5\left(x-y+1\right)\left(x+y+1\right)\\ b,=3x\left(x^2-2x+1-4y^2\right)=3x\left[\left(x-1\right)^2-4y^2\right]\\ =3x\left(x-2y-1\right)\left(x+2y-1\right)\\ c,=ab\left(a-b\right)\left(a+b\right)+\left(a+b\right)^2\\ =\left(a+b\right)\left(a^2b-ab^2+a+b\right)\\ d,=2x\left(x^2-y^2-4x+4\right)=2x\left[\left(x-2\right)^2-y^2\right]\\ =2x\left(x-y-2\right)\left(x+y-2\right)\)

27 tháng 8 2018

C=(2x-1)(x-1)(2x^2-3x-1)+2017

=(2x^2-3x+1)(2x^2-3x-1)+2017

=(2x^2-3x)^2-1+2017

=(2x^2-3x)^2+2016>=2016

Dấu = xảy ra khi 2x^2-3x=0

=>x=0 hoặc x=3/2

D=(x-1)(x-6)(x-3)(x-4)+10

=(x^2-7x+6)(x^2-7x+12)+10

=(x^2-7x)^2+18*(x^2-7x)+72+10

=(x^2-7x+9)^2+1>=1

Dấu = xảy ra khi x^2-7x+9=0

=>\(x=\dfrac{7\pm\sqrt{13}}{2}\)

21 tháng 10 2023

a: Sửa đề: \(2A+\left(2x^2+y^2\right)=6x^2+5y^2-2x^2y^2\)

=>\(2A=6x^2+5y^2-2x^2y^2-2x^2-y^2\)

=>\(2A=4x^2+4y^2-2x^2y^2\)

=>\(A=2x^2+2y^2-x^2y^2\)

b: \(2A-\left(xy+3x^2-2y^2\right)=x^2-8y+xy\)

=>\(2A=x^2-8y+xy+xy+3x^2-2y^2\)

=>\(2A=4x^2+2xy-8y-2y^2\)

=>\(A=2x^2+xy-4y-y^2\)

c: Sửa đề: \(A+\left(3x^2y-2xy^2\right)=2x^2y+4xy^3\)

=>\(A=2x^2y+4xy^3-3x^2y+2xy^2\)

=>\(A=-x^2y+4xy^3+2xy^2\)

a: Ta có: \(A=x^2-2xy+5y^2+4y+51\)

\(=x^2-2xy+y^2+4y^2+4y+1+50\)

\(=\left(x-y\right)^2+\left(2y+1\right)^2+50\ge50\forall x,y\)

Dấu '=' xảy ra khi \(x=y=-\dfrac{1}{2}\)

27 tháng 9 2021

a) \(A=x^2-2xy+5y^2+4y+51=\left(x^2-2xy+y^2\right)+\left(4y^2+4y+1\right)+50=\left(x-y\right)^2+\left(2y+1\right)^2+50\ge50\)

\(minA=50\Leftrightarrow x=y=-\dfrac{1}{2}\)

c) \(C=\dfrac{9}{-2x^2+4x-7}=\dfrac{9}{-2\left(x^2-2x+1\right)-5}=\dfrac{9}{-2\left(x-1\right)^2-5}\ge\dfrac{9}{-5}=-\dfrac{9}{5}\)

\(minC=-\dfrac{9}{5}\Leftrightarrow x=1\)

d) \(10x^2+4y^2-4xy+8x-4y+20=\left[4y^2-4y\left(x+1\right)+\left(x+1\right)^2\right]+\left(9x^2+6x+1\right)+18=\left(2y-x-1\right)^2+\left(3x+1\right)^2+18\ge18\)

\(minD=18\Leftrightarrow\) \(\left\{{}\begin{matrix}x=-\dfrac{1}{3}\\y=\dfrac{1}{3}\end{matrix}\right.\)

e) \(E=9x^2+2y^2+6xy-6x-8y+10=\left[9x^2+6x\left(y-1\right)+\left(y-1\right)^2\right]+\left(y^2-6x+9\right)=\left(3x+y-1\right)^2+\left(y-3\right)^2\ge0\)

\(minE=0\Leftrightarrow\) \(\left\{{}\begin{matrix}x=-\dfrac{2}{3}\\y=3\end{matrix}\right.\)